Factors influencing job satisfaction in commercial bank / Nur Faqihah Mohd Hatta - Mohd Hatta, Nur Faqihah (Faculty of Business and Management, 2016)
Job satisfaction has a broad practice in scientific research, as well as in everyday life, there is still no common agreement about what is the real meaning of job satisfaction is. Infect there is no fixed definition on what job satisfaction is actually means. Therefore, before a definition on job satisfaction can be agreed, the nature and importance of work must be considered. Different authors have different styles towards of defining job satisfaction. Some commonly cited definitions on job satisfaction are analyzed in the text follows. Hoppock defined job satisfaction as any combination of psychological, physiological and environmental circumstances that cause a person honestly to say I am satisfied with my work (Hoppock, 1935). According to these approach findings, job satisfaction influenced by many external factors, it is like internal emotion that has to do with the way how the employee feels. That is job satisfaction presents a set of factors that cause a feeling of satisfaction. While Vroom in his definition on job satisfaction focuses on the role of the employee in the workplace. Thus he said that job satisfaction as an affective orientations on the part of individuals toward work roles which they are presently occupying (Vroom, 1964). Other than that, one of the most popular cited definitions on job satisfaction is the one given by Spector is job satisfaction is about how people feel about their job and its various aspects. It has something with the extent to which people love or hate their job. That is why job satisfaction and job dissatisfaction can appear in any perspective of work situation. Job satisfaction represents a combination of positive or negative feelings that workers have towards or during they do their work. Meanwhile, when a worker employed in a business organization, he/she brings with it the needs, desires and experiences which determinate expectations that he has dismissed.